2018
DOI: 10.1097/md.0000000000013194
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of big funnel and individualized stents for management of stomach cancer with gastric outlet obstruction

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 38 publications
2
3
0
Order By: Relevance
“…The present study demonstrated that the big end double-layer uncovered SEMS had a good performance in preventing stent obstruction and migration. The incidence of stent obstruction, food impaction, and reinterventional rate was 1.4%, 2.9%, and 4.3%, respectively, which were similar to the individualized and funnel covered SEMS [ 10 , 19 ] , but much lower compared with other reports [20, 21]. Unlike the individualized and funnel SEMS [10, 19], neither distal nor proximal migration of the big end double-layer SEMS was not found in this study.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…The present study demonstrated that the big end double-layer uncovered SEMS had a good performance in preventing stent obstruction and migration. The incidence of stent obstruction, food impaction, and reinterventional rate was 1.4%, 2.9%, and 4.3%, respectively, which were similar to the individualized and funnel covered SEMS [ 10 , 19 ] , but much lower compared with other reports [20, 21]. Unlike the individualized and funnel SEMS [10, 19], neither distal nor proximal migration of the big end double-layer SEMS was not found in this study.…”
Section: Discussionsupporting
confidence: 75%
“…The incidence of stent obstruction, food impaction, and reinterventional rate was 1.4%, 2.9%, and 4.3%, respectively, which were similar to the individualized and funnel covered SEMS [ 10 , 19 ] , but much lower compared with other reports [20, 21]. Unlike the individualized and funnel SEMS [10, 19], neither distal nor proximal migration of the big end double-layer SEMS was not found in this study. In addition, the mean survival time of patients in this study was longer than those in other reports [22, 23].…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations